2014
DOI: 10.1016/j.jes.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of sulfamethazine in an activated sludge process treating swine wastewater

Abstract: Swine wastewater is an important pollution source of antibiotics entering the aquatic environment. In this work, the adsorption behavior of sulfamethazine (SMN), a commonlyused sulfonamide antibiotic, on activated sludge from a sequencing batch reactor treating swine wastewater was investigated. The results show that the adsorption of SMN on activated sludge was an initially rapid process and reached equilibrium after 6 hr. The removal efficiency of SMN from the water phase increased with an increasing concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Liquid chromatography–mass spectrometry (LC/MS, 6430 Triple Quad LC/MS; Agilent Technologies, Santa Clara, California, USA) was used to identify biological metabolic intermediates of SMZ. The analytical methods used for LC/MS measurement of the aqueous samples were described previously ( Avisar, Lester & Mamane, 2010 ; Ben et al, 2014 ; Garcia-Galan et al, 2011 ; Mansour et al, 2014 ; Yang et al, 2011 ; Yang et al, 2012 ). An Agilent TC-C 18 column (2.1 × 50 mm, 1.8 µm particle size) and a UV detector at a wavelength of 267 nm were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid chromatography–mass spectrometry (LC/MS, 6430 Triple Quad LC/MS; Agilent Technologies, Santa Clara, California, USA) was used to identify biological metabolic intermediates of SMZ. The analytical methods used for LC/MS measurement of the aqueous samples were described previously ( Avisar, Lester & Mamane, 2010 ; Ben et al, 2014 ; Garcia-Galan et al, 2011 ; Mansour et al, 2014 ; Yang et al, 2011 ; Yang et al, 2012 ). An Agilent TC-C 18 column (2.1 × 50 mm, 1.8 µm particle size) and a UV detector at a wavelength of 267 nm were employed.…”
Section: Methodsmentioning
confidence: 99%
“…SMs, one of the major antibiotics in swine wastewater, is characterized by easy migration and high bio-toxicity compared to other veterinary antibiotics. Their behaviour in wastewater has been the subject of several analyses (Baquero et al, 2008;Ben et al, 2014;Chen et al, 2012b;Xian et al, 2010). SMs dissolve relatively well in water with low logKow (0.19-0.89), and their biosorption removal from wastewater is expected to have a low potential for hydrophobic partitioning.…”
Section: Removal By Biosorptionmentioning
confidence: 99%
“…This has been confirmed by the research of Abegglen et al (2009), Yang et al (2011), andYang et al (2012), they concluded that SMs were little adsorbed onto sludge. Similarly, Ben et al (2014) assessed the adsorption behavior of SMs in activated sludge from swine wastewater, and discovered that only about 5% of SMN was adsorbed on the activated sludge when it reached equilibrium after 6 hrs. Zhou et al (2011) also drew a similar conclusion that a large proportion of SMN was found in effluents while only a small ratio was found in the sludge after treatment by activated sludge processes.…”
Section: Removal By Biosorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation process can be divided into 3 phases. The COD dropped quickly in the first 2 h, due to the absorption of the activated sludge (Ben et al, 2014). In the next 10 h, the COD decreased at a slower speed than the first 2 h by the oxidization of activated sludge.…”
Section: The Toxicity and Biodegradabilitymentioning
confidence: 98%